Pemeriksaan Mutu Malam Model yang Beredar di Yogyakarta - Dyah Irnawati; Purwanto Agustiono; Siti Sunarintyas (Faculty of Dentistry, Universitas Indonesia, 2015)
Modelling wax is an auxiliary material in acrylic denture fabrication. This material should have standard quality. Many local and imported brand of modelling waxes are distributed in Yogyakarta. The aim of this study is to examine the quality of modelling waxes in Yogyakarta. The aim of this study is to examine the quality of modelling waxes in Yogyakarta based on international standard. Seven brand of modelling waxes (Rusco tropical, Cavec Tropical, Ruby, SMIC, Anchor Brand medium, Anchor Brand Hard, and Anchor Brand Medium) were exained by ISO 12163 (ANSI/ADA no. 24) specification. The specification which were examined were general requirements (uniform shapes, free from foreign materials, smooth sheets, uniform texture, cohere if softened, and uniform dimension), special requirements (color, odor & flavour, softening, trimming and flaming), and preparation for delivery requirements (packaging and marking). The modelling waxes were stated fulfill the requirements if all 5 samples of each brands were suitable with the specification. The results showed that one brand (Cavec Tropical) fulfilled general and specific requirements, 1 brand (SMIC) only fulfilled general requirements and 3 brands (Rusco tropical, Ruby and Anchor Brand Hard) only fulfilled special requirements. No brand fulfilled preparation for delivery requirements. The conclusion of this study was no brand of modelling waxeds distributed in Yogyakarta fulfilled all requirements.